Protective effect of caffeic acid phenethyl ester on cyclosporine A-induced nephrotoxicity in rats - Gokce, A.; Oktar, S.; Aydin, M.; Ilhan, S.; Yonden, Z.; Ozkan, O. V.; Yalcinkaya, F. R. (Elsevier Science Bv, 2009)
[Abstract Not Available]